2020
DOI: 10.7554/elife.51779
|View full text |Cite
|
Sign up to set email alerts
|

Tgfβ signaling is required for tenocyte recruitment and functional neonatal tendon regeneration

Abstract: Tendon injuries are common with poor healing potential. The paucity of therapies for tendon injuries is due to our limited understanding of the cells and molecular pathways that drive tendon regeneration. Using a mouse model of neonatal tendon regeneration, we identified TGFβ signaling as a major molecular pathway that drives neonatal tendon regeneration. Through targeted gene deletion, small molecule inhibition, and lineage tracing, we elucidated TGFβ-dependent and TGFβ-independent mechanisms underlying tendo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
86
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 81 publications
(91 citation statements)
references
References 47 publications
5
86
0
Order By: Relevance
“…To better define the tenogenic phenotype of these cells, we carried out gene expression analysis at D3 and D14 by qPCR. Expression of known markers Scx , Tnmd , and Mkx was reduced in carrier treated injured limbs relative to contralateral controls at D3 ( Figure 7A ), consistent with our prior studies (8). In AP20187-treated limbs, injury induced a less predictable response.…”
Section: Resultssupporting
confidence: 91%
See 3 more Smart Citations
“…To better define the tenogenic phenotype of these cells, we carried out gene expression analysis at D3 and D14 by qPCR. Expression of known markers Scx , Tnmd , and Mkx was reduced in carrier treated injured limbs relative to contralateral controls at D3 ( Figure 7A ), consistent with our prior studies (8). In AP20187-treated limbs, injury induced a less predictable response.…”
Section: Resultssupporting
confidence: 91%
“…The close proximity of macrophages to tendon cells at D3 suggests that secreted factors from macrophages may stimulate tendon cell proliferation. While TGFβ is an attractive candidate based on our gene expression array screen and has been implicated in other macrophage depletion models of tendon healing (21, 23) as well as fetal tendon healing (35, 38), our previous studies inhibiting TGFβ signaling showed no effect on tendon cell proliferation at D3 (8). The molecular regulators for early cell proliferation is therefore still unknown.…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…Other aspects of tendon development, such as production of matrix components like fibronectin and proteoglycans, as well as collagen production and organization, may require Smad4-dependent [ 20 ] and independent [ 50 ] TGFβ1 signaling, which long-term Smad3 inhibition prohibits. Furthermore, injury in a neonatal tendon is associated with Smad2/3 activation, and Smad2/3 activation meditated by TGFβ signaling through the TGFβ type I receptor ALK4/5/7 impacts regenerative healing [ 51 ]. Another Smad protein, Smad8, has also been shown to enhance regeneration of tendon injuries when MSCs are genetically engineered to overexpress both Smad8 and its downstream target, BMP2 [ 52 , 53 ], suggesting that Smad signaling may be involved in tendon regeneration.…”
Section: Discussionmentioning
confidence: 99%